Issue: Caribou and Petroleum Development in Arctic Alaska - Cameron, R.D. (ARCTIC, 1983)
Intensive petroleum-related development on Alaska's Arctic Slope is not always compatible with the habitat requirements of barren-ground caribou (Rangifer tarandus granti). Surface alteration can result in displacement of caribou from previously occupied components of range. Although, to date, losses of habitat have been localized, apparently with no adverse effects on herd productivity, uncontrolled or improperly planned future development on state and federal lands could remove large areas of caribou habitat, with potentially serious consequences to all of the arctic herds. Caribou represent a valuable recreational and subsistence resource. State and federal land management agencies must fully acknowledge the potential conflicts associated with industrial activity and adopt conservative policies of subsurface leasing and surface development.Key words: caribou, petroleum development, disturbance, Alaska